The possible application of intelligent systems in traditional courtyard houses in Iraq - Agha, R H M (Applied Engineering and Technology, 2022)
The focus on the Intelligent System (IS) in our existing types of building is a question of suitability, rather than creativity to enhance the building performance. This research explores the possible application of IS in improving the performance of courtyard houses in Baghdad, Iraq by answering the research two questions which are Q1: What does the traditional courtyard house (TCH) contain that should enhanced its performance? Q2: How (IS) could be added to the TCH in Iraq? The investigation which was done through literature review of courtyard houses type as seen beside intelligent building is supported by case studies investigation 12 (TCH) in Al-Kadhimiya through physical survey, observation, and documentation, in addition to 24 semi structure interviews with occupants of the same houses, and then using the qualitative method to analyse the data collection. The key findings highlight the need for adding new systems and architectural values to such TCH which is the basis of adding intelligence systems in such houses to enhance their performance. This could be improving the partial control of the environment related to structure and materials; decreasing the environmental challenges related to the ease of making modifications, the role of government regulations, and modernization requirements. Minimizing social struggles related to the idea of place psychology. Therefore, the current study concludes that the TCH could be as a contender of IS to enhance its performance through retrofit of such houses that contain high architectural value and re-build these houses with low architectural value and slum structure.